Simple and Multiple Relationships between Big-Five Personality Dimensions and Addiction in University Students - Y Zargar; M Ghaffari (Tehran University of Medical Sciences, 2009)
"nBackground: This study aimed at investigating the simple and multiple relationships between   personality traits and addiction potential in university students."nMethods: Three hundred and forty two students were selected by cluster sampling from the Shahid Chamran University (Iran). The scales used for this descriptive study were NEO-FFI personality inventory and Iranian Addiction Potential Scale (IAPS). To analyze the data, we used descriptive and inferential statistic test via spss-13."nResults: There were simple and multiple relationships between personality traits and addiction potential. Multiple regression analysis (stepwise method) showed that neuroticism, conscientiousness and agreeableness had significant multiple correlation with addiction potential (F=32.89, P<0.001). The components of openness and extroversion eli-minated from regression."nConclusion: Personality traits predicted addiction potential in university students. The most important suggestion of this research was to pay attention scientifically to personality characters as a fundamental factor of this difficulty, rather than just emphasizing on the cessation of drug or alcohol using.